1996
DOI: 10.1055/s-2007-994312
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Preterm Labor with the Oxytocin Antagonist Atosiban

Abstract: The purpose of this study was to describe the course of preterm labor in patients receiving a standard intravenous infusion of the oxytocin antagonist atosiban. An open-labeled, non-randomized study was conducted at 4 sites. Successful tocolysis was defined as delay of delivery larger than 48 hours from starting atosiban and no need for an alternate tocolytic. Atosiban was administered by continuous intravenous infusion at a rate of 300 micrograms per minute until uterine contractions were absent for 6 hours, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 4 publications
0
42
0
4
Order By: Relevance
“…Earlier studies of atosiban in the treatment of preterm labour have shown that the inhibition of uterine contractility by intravenous administration was associated with a delay in delivery at least comparable to that of other tocolytic agents 20,21,24 . Goodwin et al…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies of atosiban in the treatment of preterm labour have shown that the inhibition of uterine contractility by intravenous administration was associated with a delay in delivery at least comparable to that of other tocolytic agents 20,21,24 . Goodwin et al…”
Section: Discussionmentioning
confidence: 98%
“…Because (i) 125 I-ZOTA displays an equivalent affinity for the human OTR and the human V 1a receptor, (ii) several residues involved in the binding of all classes of antagonists are conserved throughout the AVP/OT receptor family, and (iii) OTR and V 1a share a significant sequence identity in the upper part of TMD II, TMD III, TMD VI, and TMD VII as well as in the first extracellular loop, we propose that binding sites for 125 I-ZOTA in the OTR and V 1a receptor could be equivalent. However, to allow a more complete definition of the binding sites of the OTR for cyclic peptide antagonists such as 125 I-ZOTA or Atosiban (14,15) and to generate meaningful information on receptor/antagonist interactions, it will be necessary to perform other photolabeling studies.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of such OT antagonists has been demonstrated clinically by using intravenously administered 1-deamino[DTyr(Et) 2 ,Thr 4 ,Orn 8 ]vasotocin (Atosiban). This peptide antagonist has been shown to inhibit uterine contractions in women with threatened and established preterm labor (14,15). However, the structure/function relationships of the functional domains of the OTR and the topography of the ligand-binding sites are still poorly investigated.…”
mentioning
confidence: 99%
“…[35][36][37] For atosiban, no significant fall in DBP occurred, which is consistent with earlier work. [3,32,38,39] …”
Section: Sphygmomanometer Blood Pressurementioning
confidence: 99%